How best to support livelihoods of blacksmiths with minimum impact on forest products - Rijal, Rajan; Chhetri, Ran Bahadur; Ricardo, Rozzi (Himalayan Journal of Sciences, 2011)
None DOI: http://dx.doi.org/10.3126/hjs.v7i9.2338 Himalayan Journal of Sciences Vol.7 Issue 9 2011 pp.7-8